Dihydroneopterin and the generation of superoxide from iron ions - Oettl Karl; Greilberger Joachim; Reibnegger Gilbert (Pteridines, 2000)
We describe the impact of dihydroneopterin on the formation of superoxide radicals. As radical source ferrous iron in air-saturated aequeous solution was used. Detection of superoxide was achieved using reduction of nitroblue tetrazolium to formazan. Dihydroneopterin decreases formazan formation when high concentrations of ferrous iron are used which induce a rapid superoxide formation within minutes. On the other hand, when low concentrations of ferrous iron are used, addition of dihydroneopterin to the assay mixture leads to an increase ir. formazan formation for several hours of incubation. We therefore conclude that the radical promoting activity of dihydroneopterin is physiologically more relevant compared to its radical scavenging properties.